A newly developed strain of Enterococcus faecium isolated from fresh dairy products to be used as a probiotic in lactating Holstein cows - Azzaz, Hossam H.; Kholif, Ahmed E.; Murad, Hussein A.; Vargas-Bello-Pérez, Einar (Frontiers in Veterinary Science, 2022)
The objective of this study was to determine the ability of an isolated and identified Enterococcus faecium EGY_NRC1 bacteria as a probiotic for lactating cows. Two experiments were conducted: In Experiment 1, the effect of three levels (1, 2 and 3 g/kg diet, DM basis) of isolated and commercial E. faecium on in vitro ruminal fermentation kinetics. In Experiment 2, thirty multiparous Holstein cows (633 ± 25.4 kg body weight) with 7 days in milk, were randomly assigned to 3 treatments in a completely randomized design in a 60-day experiment. Cows were fed without any additives (control treatment) or supplemented with 2 g/kg feed daily of E. faecium EGY_NRC1 (isolated to contain 1.1 × 109 CFU/g) or commercial E. faecium NCIMB 11181 (isolated to contain 2 × 1012 CFU/g). The isolated E. faecium linearly and quadratically increased (P<0.001) total gas production (TGP), the degradability of dry matter (dDM) and organic matter (dOM) while decreased (P<0.05) methane (CH4) percent of total gas production, CH4 production, and pH. The commercial E. faecium increased TGP and decreased proportional CH4 (P<0.01) while decreased (P<0.01) CH4 production, pH and increased the dDM and dOM, short chain fatty acids and ruminal NH3-N concentration. The isolated E. faecium increased (P<0.01) the digestibility of DM, neutral and acid detergent fibers, daily milk production and feed efficiency compared to the control treatment without affecting feed intake. Moreover, the isolated E. faecium increased (P<0.05) the proportion of C18:1 trans-9, C18:2 cis-9-12 and C18:2 trans-10 cis-12. Treatments did not affect milk composition. Both isolated and commercial E. faecium improved (P<0.01) OM, crude protein and nonstructural carbohydrates digestibility, increased serum glucose (P=0.002) and decreased serum cholesterol (P=0.002). Additionally, both E. faecium strains decreased C23:0 (P=0.005) in milk. In conclusion, the use of E. faecium (isolated and commercial) improved feed efficiency and production performance, with superior effects on animal performance from isolated E. faecium compared to the commercial one.